Recent advances in trypanosomatid research: genome organization, expression, metabolism, taxonomy and evolution - Maslov, Dmitri A; Opperdoes, Fred R; Kostygov, Alexei Yu; Hashimi, Hassan; Lukeš, Julius; Yurchenko, Vyacheslav (Parasitology, 2019)
Unicellular flagellates of the family Trypanosomatidae are obligatory parasites of invertebrates, vertebrates and plants. Dixenous species are aetiological agents of a number of diseases in humans, domestic animals and plants. Their monoxenous relatives are restricted to insects. Because of the high biological diversity, adaptability to dramatically different environmental conditions, and omnipresence, these protists have major impact on all biotic communities that still needs to be fully elucidated. In addition, as these organisms represent a highly divergent evolutionary lineage, they are strikingly different from the common 'model system' eukaryotes, such as some mammals, plants or fungi. A number of excellent reviews, published over the past decade, were dedicated to specialized topics from the areas of trypanosomatid molecular and cell biology, biochemistry, host-parasite relationships or other aspects of these fascinating organisms. However, there is a need for a more comprehensive review that summarizing recent advances in the studies of trypanosomatids in the last 30 years, a task, which we tried to accomplish with the current paper.
Keywords: fylogeneze; Biological Evolution; Genome, Protozoan; Animals; Humans; Gene Expression Regulation; lidé; Phylogeny; zvířata; genom protozoální; biologická evoluce; regulace genové exprese; Trypanosomatina